Freedom and the Internet? - Galindo, Fernando; Moura do Carmo, Valter (DIXI, 2017)
Purpose: The article provides a reflection on the limits established by the use of the Internet on exercising the right to freedom. This is recognized in democratic constitutions as the preservation of the exercise of the autonomy of will in the daily life of citizens or individuals, which are part of a specific social and political organization, by respecting its exercise by other individuals or citizens. Description: The work especially intends to present some limits that are set in this regard in several practices that take place on the Internet. Point of view and conclusions: It provides arguments focused on considering to what extent an effective, positive, complete and absolute relationship between freedom and the Internet can be established, if possible.